"Because you have Talked about your Feelings, you Don't Have to Think about them in School": Experiences of School-Based Counselling for Primary School Pupils in Northern Ireland. Issue 3 (2nd July 2016) - Kernaghan, Donna; Stewart, Dave
ABSTRACT: Well-being is increasingly being recognised as an important aspect of children's lives. Barnardo's Northern Ireland "Time 4 Me" school-based counselling service was established in 2007 with the purpose of providing individual counselling for primary school children and wrap-around support for parents/carers and school staff. The focus of the service is to improve the emotional well-being of pupils by helping them cope better with life problems in order to increase their learning capacity. The Time 4 Me service employs an "outcome-informed" approach and routinely administers a range of outcome tools to all service participants—pupils, parents/carers and school staff—to capture change over time and overall impact. The service employs a range of measures to track impact, including the Strengths and Difficulties Questionnaire, the Child Outcome Rating Scale and the Child Session Rating Scale. In addition, the service has created a bespoke qualitative "experience of intervention" survey to capture the views of children using the service. This article presents qualitative data collected from this survey from all pupils who used the Time 4 Me service in the academic year 2013/14. This was a total of 120 primary school pupils from 20 schools. Results indicated children accessed school-based counselling for relational problems and behaviour and emotional issues. Differences in the reasons children use counselling have been found in terms of gender and age group. Key findings presented in this article focus on what children reported they liked about counselling, what methods and strategies they found helpful, and the changes they reported in their lives.